Experimental Investigation of Surface Roughness for AA 3003-0 Aluminium Alloy Using Single Point Incremental Forming. (2021) - Dodiya, Hardik R.; Patel, Devang A.; Pandey, Akash B.; Patel, Divyangkumar D.; Saladi, Sekar
Abstract: Single point incremental forming is a sheet metal forming technique that produces intricately shaped specially made parts. A tool with a hemispherical end is used to produce continuous local plastic deformation, which improves the formability of a sheet metal blank. The surface roughness of AA 3003-O aluminium alloy was investigated in this experiment by varying tool diameter, sheet thickness, step size, and feed rate. A four-factor central composite design with four centre points is used to create a mathematical model of the design parameters that yield the best response. The Analysis of Variance (ANOVA) is used to look at the outcomes. The experiments show that surface roughness has the greatest individual impact of tool diameter, followed by step size, feed rate, and sheet thickness. The experimental results show that lower sheet thickness has no effect of tool size. The middle range of design parameters yields contradictory results. It is also discovered that surface roughness and sheet thickness have a direct relationship. With the right combination of tool diameter, feed rate, and sheet thickness, the surface finish was improved by more than 30%.